CADM1, MAL and miR124-2 methylation analysis in cervical scrapes to detect cervical and endometrial cancer. Issue 12 (3rd October 2014) - De Strooper, Lise M A; van Zummeren, Marjolein; Steenbergen, Renske D M; Bleeker, Maaike C G; Hesselink, Albertus T; Wisman, G Bea A; Snijders, Peter J F; Heideman, Daniëlle A M; Meijer, Chris J L M
Abstract : Aims: Gene promoter hypermethylation is recognised as an essential early step in carcinogenesis, indicating important application areas for DNA methylation analysis in early cancer detection. The current study was set out to assess the performance of CADM1, MAL and miR124- 2 methylation analysis in cervical scrapes for detection of cervical and endometrial cancer. Methods: A series of cervical scrapes of women with cervical (n=79) or endometrial (n=21) cancer, cervical intraepithelial neoplasia grade 3 (CIN3) (n=16) or CIN2 (n=32), and women without evidence of CIN2 or worse (n=120) were assessed for methylation of CADM1, MAL and miR124-2 . Methylation analysis was done by the PreCursor-M assay, a multiplex quantitative methylation-specific PCR. Results: All samples of women with cervical cancer (79/79, 100%), independent of the histotype, and 76% (16/21; 95% CI 58.0% to 94.4%) of women with endometrial cancer scored positive for DNA methylation for at least one of the three genes. In women without cancer, methylation frequencies increased significantly with severity of disease from 19.2% (23/120; 95% CI 12.1% to 26.2%) in women without CIN2 or worse to 37.5% (12/32; 95% CI 20.7% to 54.3%) and 68.8% (11/16; 95% CI 46.0% to 91.5%) in women with CIN2 and CIN3, respectively. Overall methylation positivity and the number of methylated genes increased proportionally to the lesion severity. Conclusions: DNA methylation analysis of CADM1, MAL and miR124-2 in cervical scrapes consistently detects cervical cancer and the majority of CIN3 lesions, and has the capacity to broaden its use on cervical scrapes through the detection of a substantial subset of endometrial carcinomas.